Preparedness of information institutions for the knowledge-based economy : a case study of the National Library Board of Singapore. - Chan, Peter Khin Meng. (2008)
This research seeks to serve as an exploratory study to assess the preparedness of selected information organizations for making a contribution toward the KBE.